FOOTWORK TRAINING MODEL AS BASIS FOR PROGRESS IN MARTIAL ARTS TECHNIQUES AND TACTICS - Lukina, A.M.; Zekrin, F.K.; Kozyreva, A.P.; Mustaev, R.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the relevant theoretical and practical study reports and survey practical footwork training experiences in the martial arts coaching community to offer an efficient martial arts footwork mastering and excellence model. Methods and structure of the study. We analyzed, for the purposes of the study, the relevant theoretical and practical literature including scientific articles, monographs and dissertations; plus surveyed the martial arts coaches (n=17) to study their practical footwork mastering and excelling experiences classifiable by the technical and tactical skill training stages. Results and conclusion. Modern martial arts theoreticians and practitioners commonly interpret footwork as the continuous movement with the reasonably versatile footwork style, skills and combinations. A successful and efficient footwork style is known to facilitate the individual technical and tactical skill set being used in a most cost-efficient and resultant manner. Footwork may be also referred to as maneuvering that means the purposeful and rational individual movement control and style as a basis for success in tactical goals. Maneuvering will be basically designed to control distance and facilitate positioning for attacks and defenses. Our analysis of the theoretical and practical study reports and survey of the practical footwork training experiences of the martial arts coaches found the existing footwork training methods dominated by the traditional physical fitness, special conditioning and special fitness practices. The survey found that martial arts coaches striving to apply a wide range of traditional footwork mastering and excelling tools albeit still tend to underestimate and underuse modern patterned/ modular footwork training methods and special martial arts games.